Actualization of the Invariant Semantics of the STAR Symbol in Texts of Russian Rock Poetry - Ivan A. Avdeenko (Научный диалог, 2020)
The questions of the invariant semantics of the symbol and its actualization in the texts of Russian rock poetry are considered. Attention is paid to the studies of the symbol, concept and image of the star in Russian poetry and rock poetry. The author notes that these studies do not present the correlation of individually authored imaginative worldview with the worldview of the subculture reflected in the text. A review of the work of linguistic poetics and anthropocentric linguistics is performed. The definitions of a symbol within the framework of these paradigms are given. It is concluded that the understanding of a symbol as a carrier of the worldview of culture changes the idea of the connection between the signifier and the signified and the “reference point” of the aesthetic. The author proceeds from the fact that the aesthetic image is built on the basis of the invariant semantics of a symbol in the language of subculture. The results of a comparative analysis of the symbolic semantics of the star nomination in the language of Russian rock poetry and other subsystems of the Russian national language, including aesthetically oriented ones, are presented. It is shown that the invariant semantics of the STAR symbol, relevant for Russian rock poetry, lies at the heart of the star’s images, which are identical, connected and contrasted with the author’s image. It is proved that the actualization of the semantics of the STAR symbol does not depend on the specific author and the text of Russian rock poetry, reproduces general ideas about the world.